ANALISIS BERPIKIR KRITIS MATEMATIS SISWA SMP PADA MATERI STATISTIKA - Arum Putri Titis Prastianti; Wharyanti Ika Purwaningsih; Isnaeni Maryam (Jurnal Karya Pendidikan Matematika, 2022)
This study aims to analyze the mathematical critical thinking of junior high school students on statistical material. This type of research is qualitative research. The subjects of this study were 2 students of class VIII who had been selected purposively, specifically students with high mathematical abilities. Data collection techniques used questions, interviews, field notes, and documentation. The main instrument in this research is the researcher himself who is supported by a critical thinking test instrument for statistical material in the subsection average or mean. The data analysis technique uses three stages, namely data reduction, data presentation, and drawing conclusions. The validity test in this study is a credibility test with triangulation techniques, namely observation, tests, and interviews. The results of this study indicate that students with high mathematical abilities can fulfill all critical thinking indicators in statistical material. The indicators are interpretation, analysis, explanation, evaluation, self-regulation, & inference.